A Lipophilic 4‐Phenylbutyric Acid Derivative That Prevents Aggregation and Retention of Misfolded Proteins. Issue 8 (27th January 2020) - Azoulay‐Ginsburg, Salome; Trobiani, Laura; Setini, Andrea; Favaloro, Flores Lietta; Giorda, Ezio; Jacob, Avi; Hauschner, Hagit; Levy, Laura; Cestra, Gianluca; De Jaco, Antonella; Gruzman, Arie
Abstract: Chemical chaperones prevent protein aggregation. However, the use of chemical chaperones as drugs against diseases due to protein aggregation is limited by the very high active concentrations (mm range) required to mediate their effect. One of the most common chemical chaperones is 4‐phenylbutyric acid (4‐PBA). Despite its unfavorable pharmacokinetic properties, 4‐PBA was approved as a drug to treat ornithine cycle diseases. Here, we report that 2‐isopropyl‐4‐phenylbutanoic acid (5 ) has been found to be 2–10‐fold more effective than 4‐PBA in several in vitro models of protein aggregation. Importantly, compound 5 reduced the secretion rate of autism‐linked Arg451Cys Neuroligin3 (R451C NLGN3). Abstract : The power of chaperones : Chemical chaperones have been shown to be able to prevent protein aggregation in very high active concentrations. Here, it is reported that 2‐isopropyl‐4‐phenylbutanoic acid was more potent (two‐ to tenfold) and more effective than 4‐phenylbutyric acid (4‐PBA) in several protein aggregation in vitro models.